2015
DOI: 10.1186/s12967-015-0595-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased long noncoding RNA SPRY4-IT1 contributing to gastric cancer cell metastasis partly via affecting epithelial–mesenchymal transition

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are emerging as key regulators governing fundamental biological processes, and their disorder expression involves in tumorigenesis. SPRY4-IT1 (SPRY4 intronic transcript 1), a lncRNA derived from an intron within SPRY4 gene, involves in multiple cancers development. However, the expression pattern and biological function of SPRY4-IT1 in gastric cancer is still not well documented. Hence, we carried out the present study to investigate the potential role of SPRY4-IT1 in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 32 publications
(26 reference statements)
6
81
0
Order By: Relevance
“…Xie et al 61 found that the expression of SPRY4-IT1 was significantly downregulated in GC tissues and cell lines compared with normal control. They also found that downregulation of SPRY4-IT1 was significantly correlated with GC tumor size, advanced pathological stage, deeper depth of invasion, and lymphatic metastasis.…”
Section: Gcmentioning
confidence: 99%
“…Xie et al 61 found that the expression of SPRY4-IT1 was significantly downregulated in GC tissues and cell lines compared with normal control. They also found that downregulation of SPRY4-IT1 was significantly correlated with GC tumor size, advanced pathological stage, deeper depth of invasion, and lymphatic metastasis.…”
Section: Gcmentioning
confidence: 99%
“…For instance, a lncRNA named SPRY4 intronic transcript 1 (SPRY4-IT1) was reported to be overexpressed in melanoma, renal cell carcinoma, esophageal squamous cell carcinoma, breast cancer, bladder cancer and glioma, and associated with poor prognosis and promotion of tumor growth (24)(25)(26)(27)(28)(29). Certain studies also demonstrated that SPRY4-IT1 expression was decreased in non-small-cell lung cancer and gastric cancer, and acted with significant antitumor function in these two types of cancer (30,31). Similarly, HOTTIP may exhibit a tissue-specific expression pattern and serve a different function in different types of cancer, as with SPRY4-IT.…”
Section: Discussionmentioning
confidence: 99%
“…Its down-regulation in cancer tissue seems to be based on promoter methylation. Target validation experiments in SGC 7901, BGC 823 and MKN 45 gastric cancer cells point to its role in inhibition of proliferation, colony formation, cell migration and invasion and its capacity to up-regulate cyclin D1, MMP2, MMP9 and E-cadherin and to down-regulate vimentin (158,159). Ectopic expression of SPRY4-IT in BGC 823 cells reduced the number of metastatic nodules after teil vein injection (158).…”
Section: Metastasis-related Lncrnas: Category IIImentioning
confidence: 99%
“…Tail vein injection experiments of these cells reveal promotion of lung metastases in comparison to control SGC 7901 cells (157). SPRY4-IT1 (SPRY4 intronic transcript 1) is derived from an intron of the SPRY gene and its decreased expression in gastric cancer correlates with overall survival (OS) and disease-free survival (DFS) (158,159). Its down-regulation in cancer tissue seems to be based on promoter methylation.…”
Section: Metastasis-related Lncrnas: Category IIImentioning
confidence: 99%